Image Concerns and the Political Economy of Publicly Provided Private Goods - Tobias König; Tobias Lausen; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2017)
Governments often provide their citizens with goods and services that are also supplied in markets: education, housing, nutritional assistance, etc. We analyze the political economy of the public provision of private goods when individuals care about their social image. We show that image concerns motivate richer individuals to vote for the public provision of goods they themselves buy in markets, the reason being that a higher provision level attracts more individuals to the public system, enhancing the social exclusivity of market purchases. In effect, majority voting may lead to a public provision that only a minority of citizens use. Users in the public system may enjoy better provision than users in the private system. We characterize the coalitions that can prevail in a political equilibrium.
Keywords: H42; D72; 330; in-kind provision; status preferences; majority voting